Assessment of Alamandine in Pulmonary Fibrosis and Respiratory Mechanics in Rodents - Fernandes, Renata Streck; Dias, Henrique Bregolin; de Souza Jaques, Wynnie Amaral; Becker, Tiago; Rigatto, Katya (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Introduction. Pulmonary fibrosis (PF) is characterized by an accelerated decline in pulmonary function and has limited treatment options. Alamandine (ALA) is a recently described protective peptide of the renin-angiotensin system (RAS) with essential tasks in several conditions. Our group previously demonstrated that ALA is reduced by 365% in the plasma of patients with idiopathic PF, and thus, it is plausible to believe that stimulation of this peptide could represent an important therapeutic target. In this sense, this study investigates the effects of ALA in an experimental model of PF. Materials and Methods. Bleomycin (BLM) was administrated in Wistar rats, and these fibrotic animals were treated with ALA for 14 days. Body weight, histology, respiratory, and hemodynamic parameters were analyzed to study the effects of ALA. Results. ALA treatment attenuated the development of fibrosis (P<0.0001), reduced respiratory system elastance (P<0.0001), and preserved weight gain (P<0.0001) in fibrotic animals without affecting the autonomic control of blood pressure and heart rate. Conclusion. The data from this study demonstrate the potential of ALA to alleviate pulmonary fibrosis and improve respiratory system mechanics in vivo. The promising results encourage more detailed investigations of the potential of ALA as a future and efficient antifibrotic.